Utilization of whatsapp application as discussion media in blended learning - Kawakibul Qamar; Selamet Riyadi; Tri Candra Wulandari (Journal of Education and Learning (EduLearn), 2019)
The purpose of this study is to discuss about utilization of Whatsapp application as discussion media in Blended Learning. This study sought to integrate learning technologies to improve the quality of student's learning. Messenger application is used to communicate synchronously, so it can be positioned as a discussion media. This study focused on Whatsapp capabilities can be utilized to conduct in online learning of Blended Learning. This study aims to describe the discussion media. This study through the literature review that outlines the stages of Blended Learning using Whatsapp application as a discussion media by using qualitative methods. The result shows that Whatsapp application utilization as a discussion media in Blended Learning sessions initiated by offline using conventional methods, so the online session focused on the discussion as indicated by dialogue and interaction among participants.